Early Initiation of Breastfeeding and Associated Factors Among Women of Reproductive age in Simiyu Region, Tanzania - Laura J. Shirima BScAS, MScEAB; Henry L. Mlay BSc, MScEAB; Serafina Mkuwa MD, MSc.PH; Agatha Fabian BSc.HN, MIPH, PhD; Stella E. Mushy BScN, MSN, PhD RCH; Frida N. Ngalesoni MD, MSc, PhD; Innocent B. Mboya BA, MSc, PhD; Rachel N. Manongi MD, MPhiL, PhD (SAGE Publishing, 2023)
Background Breast milk provides infants with complete nutrition for immune development and protection against childhood diseases and associated mortality. Early initiation of breastfeeding (EIBF) aids in providing colostrum to newborns, providing protection against infection, and improving newborn and infant survival. Although Simiyu reported the lowest prevalence of EIBF in Tanzania, no study has investigated the factors associated with EIBF in this region. Objective The study aimed to determine early breastfeeding initiation prevalence and associated factors among women of reproductive age in the Simiyu region. Methodology We used data from a cross-sectional study conducted by AMREF Health Africa among 669 women of reproductive age (15-49 years) in the Simiyu region, Tanzania. An interviewer-administered questionnaire collected data on breastfeeding practices (including breastfeeding initiation) among others. A multilevel logistic regression analysis estimated the adjusted odds ratio (OR) and 95% confidence intervals (CI) for factors associated with EIBF. Results The mean age of 669 women analyzed was 28.3 years (SD ± 6.8). The prevalence of EIBF was 62.2%, ranging from 52.7% in Bariadi district to 73.3% in Maswa district. Lower odds of EIBF were among women who had a caesarian section (OR = 0.41; 95% CI = 0.17-0.98) and those who gave birth to male children (OR =  0.57; 95%CI = 0.39-0.82) while higher odds of EIBF were among mothers who reported skin-to-skin contact (OR =  2.40; 95%CI = 1.53-3.83) and from Maswa district (OR = 2.73; 95%CI = 1.09-6.89). Conclusion The prevalence of EIBF in the Simiyu region remains low (62%) relative to the global target of 70% by 2030 and varies by district. To promote EIBF in the region, good engagement and communication practices between mothers and healthcare providers should be emphasised in educating women about the importance of EIBF. Moreover, the practice of skin-to-skin contact between mother and child should be encouraged immediately after delivery.